Disaster experiences, associated problems and lessons in southwestern coastal Bangladesh: exploring through participatory rural appraisal to enhance resilience. (30th January 2023) - Parvin, Gulsan Ara; Dasgupta, Rajarshi; Abedin, Md. Anwarul; Sakamoto, Masashi; Ingirige, Bingunath; Kibria, Mohammad Golam; Fujita, Kumiko; Basu, Mrittika; Shaw, Rajib; Nakagawa, Hajime
ABSTRACT: The southwestern coastal part of Bangladesh is highly vulnerable to different kinds of disasters due to the changing climatic conditions. With the lenses of rural communities here an approach to examine how were the different disasters experiences, what lesson they learnt and what are their present disaster associated problems and stakeholder's networks they rely on to enhance their resilience. Qualitative data were collected through participatory rapid rural appraisal (100–150 persons), field observation, 12 focus group discussions (25–40 people/FGD), and key informant interviews (25 people) in four southwestern coastal districts and nine coastal villages of Bangladesh. Results showed that since long back to date drinking water crisis, poor roads, poverty, poor sanitation, and health problems are the main identified disaster-associated problems. After learning lessons from previous disaster experiences, the community people have improved and changed their practices mainly by storing emergency foods, house construction, and increasing disaster awareness. However, the coastal communities are combating with the problems that have both direct and indirect association with poor infrastructures. Therefore, the coastal communities urge and sketched for a better stakeholders' supports and networks to minimize their problems and thus to enhance communities' disaster resilience.